PENGARUH KONTEN YOUTUBE NAJWA SHIHAB EPS. #DIRUMAHAJA DARI MUSISI INDONESIA TERHADAP MOTIF BERDONASI - Virda Priciliawati (2020)
In this research, we will discuss about one of Najwa Shihab's Youtube content regarding COVID-19 outbreaks which are currently in the spotlight in the State of Indonesia today, the Youtube Channel of Najwa Shihab provides content entitled Eps. #dirumahaja From Indonesian Musicians, which presents the activities of Indonesian Musicians who are holding a fundraising concert with the concept of #stayathome which shows their concern amid the corona virus outbreak in Indonesia. The theory used in this research is the Uses And Effect Theory. The approach used in this research is quantitative with explanative research types and survey methods using questionnaires. Based on the results of the correlation coefficient research conducted between Najwa Shihab Youtube Content and Donated Motives. Evidenced by the correlation test to get the results of r that is 0.878 <r table 0.960 the remaining concluded Najwa Shihab Youtube Content with Motive Donation has a very strong relationship. the hypothesis that is valid or accepted is Ha = rxy (rxy> 0) ≠ 0, Ha = There is an influence of Najwa Shihab Eps Youtube Content. #stayathome From Indonesian Musicians Against Motive to Donate. Then H0 is rejected and Ha is accepted. Keywords: Youtube Content, Motive to Donate, Uses and Effects, Quantitative